Whether the CMIP5 Models Can Reproduce the Long-Range Correlation of Daily Precipitation? - Dong, Tianyun; Zhao, Shanshan; Mei, Ying; Xie, Xiaoqiang; Wan, Shiquan; He, Wenping (Frontiers in Environmental Science, 2021)
In this study, we investigated the performance of 9 CMIP5 models for global daily precipitation by comparing with NCEP data from 1960 to 2005 based on the detrended fluctuation analysis (DFA) method. We found that NCEP daily precipitation exhibit long-range correlation (LRC) characteristics in most regions of the world. The LRC of daily precipitation over land is the strongest in summer, while LRC of precipitation in ocean is the weakest in summer. The zonal average scaling exponents of NCEP daily precipitation are smaller in middle and high latitudes than that in the tropics. The scaling exponents are above 0.9 over the tropical middle and east Pacific Ocean for the year and four seasons. Most of CMIP5 models can capture the characteristic that zonal mean scaling exponents of daily precipitation reach the peak in the tropics, and then decrease rapidly with the latitude increasing. The zonal mean scaling exponents simulated by CMCC-CMS, GFDL-ESM2G and IPSL-CM5A-MR are similar to those of NCEP, while BCC_CSM1.1(m) and FGOALS-g2 cannot capture the feature of seasonal variations of LRC of daily precipitation. The differences between the models and NCEP are larger in the middle and low latitudes, while smaller in the high latitudes. The differences of scaling exponents between CMIP5 models and NCEP are less than ±0.05 in some regions, including Arctic Ocean, Siberian, Southern Ocean, and Antarctic. However, for Western Africa, Eastern Africa, Tropical Eastern Pacific and Northern South America, the simulated biases of scaling exponents are greater than ±0.05 for the year and all the four seasons. The biases of the LRC simulated by GFDL-ESM2G, HadGEM2-AO and INM-CM4 are relatively small, which mean that the LRC characteristics of daily precipitation are well simulated by these models.